“IT’S JUST A CONSTANT EXCHANGE OF CONTAINERS”: DISTRIBUTION OF HOME-MADE FOOD AS AN ELEMENT OF POLISH FAMILY LIFESTYLES - Agata Bachórz (Etnografia Polska, 2018)
This paper deals with intergenerational home-made food transfers inside Polish urban families. It is based on the material gathered by interviewing representatives of two generations. Not only economic, but also emotional and symbolic function of food distribution are presented. The circulation of food containers which travel between parents’ and children’s households is interpreted as systemic, according to the logic of gift. Three components of the system – giving, receiving and reciprocating – are analysed in order to reveal the tensions hidden in the food exchange. The relation between stability and dynamics in contemporary Polish families is also described. Both reproduction of the social order and the intergenerational change are embodied in the system of food exchange analysed in the paper.